Non-uniform dissipation of the Antarctic ozone hole - KANE, R.P. (MAUSAM, 1994)
The evolution o f the Antarct ic ozone hole is illustrated fo r 1985·1989 and 1990 springs. A detailed study for 1986.19 89 and 1990 events indicates that the evolution. which occurs in ea rly October . is fairly unifo rm over the South Pole. Hence the fluctuations observed at Syowa, McMurdo and Palmer during this period arc mostly due to the vortex \’’3.11 passing in and out over these periferial loca t ions. However, later in November when the hole is dissipating, the vortex may shift from the South Pole in any direction and may also come back or intensify on Sou th Pole before finally disappearing. At South Pole. the recovery started by October end in 19S5. 19R6 and 1988 but later in 19R7 (November end), 1989 November beginning) and 1990 (November end •.